Dampak Kemiskinan Terhadap Kesehatan Masyarat Dalam Naskah Drama Umang-Umang Karya Arifin C. Noer dan Naskah Drama Bunga Semerah Darah Karya W.S. Rendra - Ahmad Fauzi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Literary works are a form of reflection or depiction of people's lives by using language as a medium of delivery. Arifn C. Noer and W.S. Rendra described the condition of society at that time through the works of Umang-Umang and Bunga Semerah Darah. In both texts it is told how poverty and destitution affect the lives of a person or group. Based on this topic, researchers use the literary sociology approach of Alan Swingewood. The method used is a descriptive qualitative method. Then found the results of research in the form of the narrative structure of the two texts and the influence of poverty on the condition of society at that time.